2015
DOI: 10.1097/md.0000000000002178
|View full text |Cite
|
Sign up to set email alerts
|

STROBE—Radiation Ulcer

Abstract: With increasing numbers of percutaneous coronary intervention (PCI) and complex cardiac procedures, higher accumulated radiation dose in patient has been observed. We speculate cardiac catheter intervention induced radiation skin damage is no longer rare.To study the incidence of cardiac fluoroscopic intervention induced radiation ulcer.We retrospectively reviewed medical records of those who received cardiac fluoroscopic intervention in our hospital during 2012 to 2013 for any events of radiation ulcer. Only … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 32 publications
(11 citation statements)
references
References 21 publications
(22 reference statements)
0
10
0
1
Order By: Relevance
“…This study is the first to recruit patients with RSU events to explore the relationship between PCI-related variables and RSU events. We previously emphasized the overlooked RSU events and presented their clinical pictures 13 . The RSU events always occurred a few weeks or months after prolonged PCIs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This study is the first to recruit patients with RSU events to explore the relationship between PCI-related variables and RSU events. We previously emphasized the overlooked RSU events and presented their clinical pictures 13 . The RSU events always occurred a few weeks or months after prolonged PCIs.…”
Section: Discussionmentioning
confidence: 99%
“…The RSU events always occurred a few weeks or months after prolonged PCIs. Iatrogenic skin complications are usually overlooked and underreported by physicians because the skin lesions do not become apparent until months after the PCIs 6 , 13 , 14 . A meta-analysis of 2857 CTO PCI procedures analysed from 65 studies reported only three cases with radiation-induced skin injury 6 .…”
Section: Discussionmentioning
confidence: 99%
“…This may relate to the complexity or repetitive courses required to achieve acceptable cardiac outcomes. Recently, we noticed an increasing incidence of severe radiation dermatitis in our hospital 4 . Moreover, the trend is worldwide 5 6 7 8 9 10 11 12 13 .…”
mentioning
confidence: 87%
“…The incidence of radiation-induced ulcers is not as rare as previously assumed [25]. Radiation-induced skin ulcer is a consequence of an excessively high cumulative skin dose.…”
Section: Radiation-induced Skin Injuriesmentioning
confidence: 98%